3D GIS modeling techniques for documentation and preservation of cultural heritage for Southeast Asian - Aiman, Ahmad Afiq; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias (Malaysia Remote Sensing Agency, 2018)
Documentation and preservation techniques have always been an important concern for the cultural heritage study particularly in the context of building in Southeast Asian. The recent disappearance of the high value of heritage building structured due to the urban renewal and redevelopment planning strategies lead to failure of conservation effort and achieving vision of cultural safeguarding by United Nation. This paper attempt to review an efforts that implemented in Southeast Asian countries through the 3D GIS modeling techniques by other scholars using an integration of other geospatial approach photogrammetry on laser scanning considered as a mechanism to increase the effectiveness of heritage preservation approach. The prominent sources of publications from web of science, Scopus and other related publisher have been used in summarize the finding according the latest year of 2011-2018 publications. The finding shows that the various techniques and approaches of 3D GIS modeling that implemented with considering the integration of other geospatial approach in effort to documenting and preserving cultural heritage structures in Southeast Asian. Hence, this effort brings up the technologies approaches giving a positive vibes in conservation and preservation of cultural heritage in Southeast Asian.